Digital Platforms as a Means of Developing Students’ Oral Speech Culture - Kholodniak, Olena (Journal of Cultural Analysis and Social Change, 2026)
Oral speech is regarded as a leading productive skill that ensures the practical implementation of communication. Based on the analysis of scientific literature, it is defined that oral speech culture encompasses linguistic, psychological, social, ethical, and didactic dimensions, reflecting the level of organization, normativity, and communicative effectiveness. Contemporary research emphasizes the importance of authentic communication as a factor of professional success and cognitive development. The integration of digital platforms and mobile applications provides personalized opportunities for speaking practice, fosters learner autonomy, and contributes to the shift toward a student-centred instructional model, which is particularly relevant in the context of educational transformation. Digital platforms and gamified environments offer individualized oral-speaking practice, combining adaptive learning algorithms, speech recognition, and game-based interaction. Role-based online scenarios create conditions for natural dialogue, sustain motivation, and stimulate active engagement. The incorporation of AI-powered chatbots and mobile tools expands opportunities for spoken language training, helps reduce psychological barriers, and supports the development of oral speech culture among students across traditional, remote, and blended learning formats. The research assumes that the development of students’ oral speech culture can be significantly enhanced through a structured three-stage experimental model integrating digital speaking platforms. At the initial diagnostic stage, both groups were expected to demonstrate comparable levels of oral proficiency, forming a baseline for valid comparison. During the formative stage, it was hypothesized that sustained training with Duolingo, ELSA Speak, Talkpal.ai, and GPT would accelerate progress in pronunciation, vocabulary activation, fluency, and dialogic interaction more effectively than traditional classroom practice. At the final assessment stage, the experimental group showed measurable improvement in phonetic accuracy, lexical diversity, fluency, and communicative confidence, reflected in higher monologic and dialogic performance scores. Thus, it is concluded that the digital-based methodology will yield clearer positive dynamics across key oral production criteria, confirming its pedagogical value in university language training.